2012
DOI: 10.1177/1557988312444718
|View full text |Cite
|
Sign up to set email alerts
|

What a Man Wants

Abstract: Little attention has been paid to the physical activity (PA) and nutrition behaviors of middle-aged men; thus, the aim of this study was to gather information and gain insight into the PA and nutrition behaviors of these men. Six focus group sessions were undertaken with middle-aged men ( N = 30) from regional Australia to explore the challenges and motivations to PA participation and healthy eating. Men had a good understanding of PA and nutrition; however, this was sometimes confounded by inconsistent media … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
45
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(51 citation statements)
references
References 36 publications
6
45
0
Order By: Relevance
“…Sixty-eight percent of men agreed strongly that they delay/avoid visiting a doctor at least some of the time. As reported in other studies [31, 32], work and family commitments were common reasons for delaying doctor’s visits, and expectedly, young healthy men rated these as reasons more strongly than young sick and older men. Not only were younger men more likely to self-monitor than older men, but those who scored higher on delay/avoidance behaviour, reported a higher likelihood of attending a DMHS.…”
Section: Discussionsupporting
confidence: 66%
“…Sixty-eight percent of men agreed strongly that they delay/avoid visiting a doctor at least some of the time. As reported in other studies [31, 32], work and family commitments were common reasons for delaying doctor’s visits, and expectedly, young healthy men rated these as reasons more strongly than young sick and older men. Not only were younger men more likely to self-monitor than older men, but those who scored higher on delay/avoidance behaviour, reported a higher likelihood of attending a DMHS.…”
Section: Discussionsupporting
confidence: 66%
“…These barriers were also identified in several other studies. For example, men in the Caperchione et al (2012) study indicated that they lacked the time to participate in regular physical activity because of family and child care commitments. While the participants in the current study also mentioned family commitments and fitting in with the family's schedule outside of working hours, long working hours and excessive workloads were more commonly identified in relation to time constraints.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the Caperchione et al (2012) study, participants were asked questions not only related to physical activity but also about sedentary time.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations